Thermal and radiative effects on unsteady MHD flow of Casson fluid past a rotating porous medium with variable mass diffusion - J. Prakash; A. Selvaraj; P. Ragupathi; Qasem M. Al-Mdallal; S. Saranya (Case Studies in Thermal Engineering)
This research examines the radiative components in heat and mass transfer phenomena in an unsteady MHD flow of Casson fluid past a vertical plate, set in a rotating porous medium. The fluid on the surface of the plate is maintained at a constant temperature while the mass transfer is set to vary. To examine the impact of heat generation, radiation, and variable mass diffusion on the velocity, temperature, and concentration profiles, the appropriate models are devised. The governing nonlinear partial differential equations are addressed through the use of Laplace transformations. The findings indicate that buoyancy forces imparted by the Grashof numbers considerably increase the velocity due to convection currents. However, the magnetic parameter counteracts velocity due to the Lorentz force while larger porosity increases fluid flow. Furthermore, radiation was demonstrated to decrease velocity and temperature from loss of heating while heat transfer increased temperature and velocity by injecting energy into the system. From the above results it can be seen that there are applications of these findings in the industrial and environmental context for example during MHD flow and filtration processes.